2005
DOI: 10.1093/brain/awh584
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein redistributes to neuromelanin lipid in the substantia nigra early in Parkinson's disease

Abstract: The distribution and tempo of neuronal loss in Parkinson's disease correlates poorly with the characteristic and more widely spread intracellular changes associated with the disease process (Lewy bodies and Lewy neurites). To determine early intracellular changes in regions where cell loss is most marked (dopaminergic A9 substantia nigra) versus regions with Lewy bodies but where cell loss is limited, we assessed 13 patients with definite Parkinson's disease at various disease stages in comparison with control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
135
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(150 citation statements)
references
References 74 publications
13
135
0
2
Order By: Relevance
“…It should be noted that A9 dopaminergic neurons, which contain a high level of α-Syn (48,49) and increased pigmentation by neuromelanin in the early stage of PD before producing Lewy bodies (12,50,51), exhibit early vulnerability. Analysis of brain samples from PD patients showed that the optical density of neuromelanin increased together with α-Syn accumulation around the neuromelanin granules in A9 neurons (51), and α-Syn was found to be a major proteic component, cross-linked to neuromelanin from brains of PD patients (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that A9 dopaminergic neurons, which contain a high level of α-Syn (48,49) and increased pigmentation by neuromelanin in the early stage of PD before producing Lewy bodies (12,50,51), exhibit early vulnerability. Analysis of brain samples from PD patients showed that the optical density of neuromelanin increased together with α-Syn accumulation around the neuromelanin granules in A9 neurons (51), and α-Syn was found to be a major proteic component, cross-linked to neuromelanin from brains of PD patients (52).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of brain samples from PD patients showed that the optical density of neuromelanin increased together with α-Syn accumulation around the neuromelanin granules in A9 neurons (51), and α-Syn was found to be a major proteic component, cross-linked to neuromelanin from brains of PD patients (52). These observations showed that the enhanced dopamine oxidation and the high level of α-Syn are specific features of A9 neurons, which provide favorable environments for the generation of large α-Syn oligomers (17).…”
Section: Discussionmentioning
confidence: 99%
“…Noradrenergic neurons are relatively well preserved in the LC of patients with early PD, and they undergo different intracellular changes from the SNc. 20 Reports indicate that the signal intensity of the LC on NmMRI is significantly reduced in PD. 8 We identified significant signal reductions in the LC of patients with late PD, which suggests that lesions emerge in the LC during late PD.…”
Section: Discussionmentioning
confidence: 99%
“…However, Lewy pathology can correlate poorly with neuronal loss in specific areas, thus its validity in predicting neuronal disintegration is questionable [29]. In fact, noradrenergic neurons in the LC are relatively preserved in early PD and do not exhibit the same intracellular changes as in the substantia nigra [30].…”
Section: In Vivo Versus Anatomopathological Studiesmentioning
confidence: 99%